Regulatory Effect of Endothelial Dysfunction and Microcirculation Pathology in Pregnant Women Diagnosed with Diabetes Mellitus - Tatiana Avramenko (Journal of Global Pharma Technology, 2018)
The steady incidence of pregnant women diagnosed with diabetes mellitus in the world stimulates the development of research in this direction and deserve special attention. This article presents new methods in usage factors of endothelial dysfunction in development complications of pregnancy with diabetes mellitus. Aim of this research was to study role of endothelial factors in development of obstetrical and perinatal pathology in pregnant women diagnosed with diabetes mellitus. This paper presents the results of the study of 120 pregnant women diagnosed with diabetes mellitus. They were grouped according to the pregnancy complications (pre-eclampsia) and fetal disorders (moderate and severe asphyxia). The researchers defined blood content of prostaglandins Е2 and F2а, prostacyclin, thromboxane, endotheline-1, nitrogen oxide and L-arginine. It was established that the decreased concentration of prostaglandins, nitrogen oxide and L-arginine combined with considerable increase of the thromboxane and endothelin in the recent pregnancy period is an unfavorable prognostic factor for the subsequent pregnancy development course and pregnancy outcome. The decreased concentration of prostaglandins, NO and L-arginine combined with considerable increase of thromboxane and endothelin content in early pregnancy period is an unfavorable prognostic factor of the pregnancy development and outcome. The administration of therapy aimed at correction of the endothelial dysfunction is path genetically grounded, and its timely administration will provide for the decrease of incidence of pregnancy disorders and obstetrical pathologies in diabetic pregnant women.Keywords: Pregnancy, Diabetes Mellitus, Endothelial Dysfunction, Obstetrical Pathology, Microcirculation, Diabetic Fetopathy.